Relationship Between T-Cell Responses to CMV, Markers of Inflammation, and Frailty in HIV-uninfected and HIV-infected Men in the Multicenter AIDS Cohort Study. (26th February 2018) - Margolick, Joseph B; Bream, Jay H; Nilles, Tricia L; Li, Huifen; Langan, Susan J; Deng, Shane; Wang, Ruibin; Wada, Nikolas; Leng, Sean X
Abstract : The magnitude of CD4 and CD8 T-cell responses to CMV antigens correlated strongly with markers of immune activation, and significantly predicted onset of frailty in nonfrail HIV-uninfected men. These responses may influence immune activation in people with chronic CMV infection. Abstract: Background: Both aging and treated human immunodeficiency virus (HIV)-infected populations exhibit low-level chronic immune activation of unknown etiology, which correlates with morbidity and mortality. Cytomegalovirus (CMV) infection is common in both populations, but its relation to immune activation is unknown. Methods: T cells from men who have sex with men (22 virologically suppressed HIV +, 20 HIV − ) were stimulated with peptides spanning 19 CMV open reading frames, and intracellular cytokine responses were assessed. Soluble and cellular inflammatory markers were assessed by multiplex electrochemiluminescence and flow cytometry, respectively. Frailty was assessed by the Fried criteria. Results: All men had responses to CMV. Proportions of CMV-responsive T cells correlated strongly ( r ≥ 0.6 or ≤ −0.6; P < .05) with immunologic markers, depending on donor HIV and frailty status. Markers significantly correlated in some groups after adjustment for multiple comparisons included interferon-γ, tumor necrosis factor-α, interleukin-6, and several chemokines in serum, and the proportion of activated T cells. The magnitude of the CD4 IL-2 response significantly predicted onset of frailty in HIV − nonfrail men, but not in HIV + nonfrail men. Conclusions: T-cell responses to CMV may strongly influence chronic immune activation in HIV-uninfected and virologically suppressed HIV-infected men, and may predict frailty in HIV-uninfected men.